Impact of Maternal Vitamin D Status on the Formation of Atopic Dermatitis in Young Children - Mariam Petriashvili PhD Student (SAGE Publishing, 2021)
Recent studies have highlighted relationship of allergic diseases with vitamin D deficiency. The aim of the study was to evaluate the impact of maternal vitamin D levels in pregnancy on the formation of atopic dermatitis in early life. A total of 186 pregnant women and their infants who developed atopic dermatitis before the age of 2 years were involved in the prospective study. Most pregnant women (57.5%) were diagnosed with 25(OH)D deficiency (3.6 ± 4.4 ng/ml) ( P  = .000). Maternal 25(OH)D deficiency was directly related to atopic family anamnesis and relatively high IgE levels. In these cases, children developed atopic dermatitis before the age of 6 months (70.8%) with prevalence of moderate-severity (55%) and persistent course (68.3%) of the disease. The above mentioned supported the idea that the peculiarities of the formation of atopic dermatitis in young children are associated with low concentrations of vitamin D in mothers during pregnancy.